The ‘Nirai’ Guitar (‘Ichigo ichie’) of Okinawa Japan - Ezra Alfandy, M Duin; Sinin, Hamdan; Khairul Anwar, Mohamad Said; Aaliyawani Ezzerin, Sinin; Ahmad Faudzi, Musib; Harini, Sosiati (North Carolina State University, 2025)
‘Nirai’ instrument combined the ‘sanshin’ and guitar. It is a mix of the ‘sanshin’ and the guitar. Instead of using the guitar's tuning, ‘nirai’ is tune like a ‘sanshin’. The ‘nirai’ sound were digitally captured using a PicoScope oscilloscope. The outcomes were subsequently examined utilizing PicoScope software (version 6), emphasizing Fast Fourier Transform FFT. The standard ‘sanshin’ tuning is a fifth, a root, and a fifth, so in the key of C, that would be G, C, G (GCG). When a low C (C) is added in ‘nirai’ it makes the tuning a root, fifth, root, fifth. In this work, the ‘nirai’ is being tune into the key of G, the 4th string of ‘nirai’ can be identified as G2 (100Hz), 3rd string as D3 (147 Hz), 2nd string as G3 (197Hz), and 1st string as D4 (296Hz). String 3 and 4 displayed 25 partials frequencies. String 1 and 2 displayed only 12 and 19 partials frequencies respectively. The partials of the overtones confirmed the typical sound quality of ‘nirai’ guitar. The thin string had less partials compared to the thick string. The partials are all integer number of harmonics with 24th, 17th and 13th harmonics missing in string 4, 3 and 2. All harmonics appear in string 1. Even though the numbers of partials are different, with the sensation of a wooden guitar-like sound, the ‘nirai’ guitar displayed similar timbre from every string.